2022
DOI: 10.54227/mlab.20220010
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-decorated carbon nanotubes as cathode catalysts for Li-CO2 batteries with a highly efficient direct Li2CO3 formation/decomposition capability

Abstract: Rechargeable Li-CO2 batteries are regarded as the ideal application for the superior energy storage technology. However, they still limited by the lack of high efficiency electrocatalyst and limited understanding for the electrochemical reaction mechanism. In this work, we prepared the Ir-CNT composite by a rotation hydrothermal method, which remarkably promoted the reaction kinetics and enhanced the electrocatalytic performance of Li-CO2 batteries. The incorporation of Ir nanoparticles shows high activity enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The Ir 4f region was deconvoluted to obtain four peaks, as illustrated in Figure S5d. The presence of two distinct peaks around 61.8 and 64.8 eV can be ascribed to the Ir 4f 7/2 and Ir 4f 5/2 peaks of Ir NPs, while the peaks at 62.5 and 65.5 eV are indicative of the presence of Ir–O bonds. , The XPS analysis confirmed that Ir–O–Co bonds were formed between Ir and Co-BPDC, which are anticipated to improve the HER activity of Ir@Co-BPDC.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The Ir 4f region was deconvoluted to obtain four peaks, as illustrated in Figure S5d. The presence of two distinct peaks around 61.8 and 64.8 eV can be ascribed to the Ir 4f 7/2 and Ir 4f 5/2 peaks of Ir NPs, while the peaks at 62.5 and 65.5 eV are indicative of the presence of Ir–O bonds. , The XPS analysis confirmed that Ir–O–Co bonds were formed between Ir and Co-BPDC, which are anticipated to improve the HER activity of Ir@Co-BPDC.…”
Section: Resultsmentioning
confidence: 69%
“…The presence of two distinct peaks around 61.8 and 64.8 eV can be ascribed to the Ir 4f 7/2 and Ir 4f 5/2 peaks of Ir NPs, while the peaks at 62.5 and 65.5 eV are indicative of the presence of Ir−O bonds. 60,61 The XPS analysis confirmed that Ir−O−Co bonds were formed between Ir and Co-BPDC, which are anticipated to improve the HER activity of Ir@Co-BPDC. Motivated by the distinctive electronic configuration and anticipated makeup of the autonomous Ir@Co-BPDC electrode, the electrocatalytic performance for HER in 1.0 M KOH solution was examined by employing a conventional three-electrode setup.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…22 From both economic and environmental points of view, there is of great significance to recycle spent LIBs. [23][24][25][26][27][28][29] Particularly, recycling the valued components (i.e., cathode, anode, and current collectors) in spent LIBs is an efficient strategy to address the challenge of resource scarcity. 30 Meanwhile, it can effectively reduce environmental destruction due to the excessive exploitation of resources.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte is generally made of lithium salts dissolved in high‐purity organic solvents, while the separator is polyolefin‐based porous membranes 22 . From both economic and environmental points of view, there is of great significance to recycle spent LIBs 23–29 . Particularly, recycling the valued components (i.e., cathode, anode, and current collectors) in spent LIBs is an efficient strategy to address the challenge of resource scarcity 30 .…”
Section: Introductionmentioning
confidence: 99%